Vertigo in children - A review - Swain, Santosh; Behera, Ishwar Chandra; Rajvanshi, Pranay (Indian Journal of Child Health, 2022)
Vertigo is a morbid symptom in the pediatric age group. It is not an uncommon clinical presentation in children. The etiopathology of vertigo in children is different from that of the adult age group. It is often not easy to evaluate this symptom in pediatric age group. In most cases, the children do not express their symptoms in detail and so clinicians cannot obtain adequate history and determine their exact etiology for vertigo. The benign paroxysmal vertigo is a common etiology in younger children, whereas the vestibular migraine is responsible for vertigo in majority of older children. Hence, pediatricians, otorhinolaryngologists, physicians, and neurologists often face difficulty in establishing the appropriate diagnosis of vertigo in children. The diagnosis of vertigo in children includes a detailed history, clinical examination, complete neurological examination, and audiological assessment. The treatment of vertigo in children includes the treatment of appropriate etiology. The prognosis of vestibular function recovery in children is often variable and unpredictable. Imaging such as computed tomography scans or magnetic resonance imaging is done in selected cases. The objective of this review article is to familiarize the readers with these complex disorders of children and with the current protocols in their management.